Evaluation of Next-Generation H3 Influenza Vaccines in Ferrets Pre-Immune to Historical H3N2 Viruses - Allen, James D.; Ross, Ted M. (Frontiers in Immunology, 2021)
Each person has a unique immune history to past influenza virus infections. Exposure to influenza viruses early in life establishes memory B cell populations that influence future immune responses to influenza vaccination. Current influenza vaccines elicit antibodies that are typically strain specific and do not offer broad protection against antigenically drifted influenza strains in all age groups of people. This is particularly true for vaccine antigens of the A(H3N2) influenza virus subtype, where continual antigenic drift necessitates frequent vaccine reformulation. Broadly-reactive influenza virus vaccine antigens offer a solution to combat antigenic drift, but they also need to be equally effective in all populations, regardless of prior influenza virus exposure history. This study examined the role that pre-existing immunity plays on influenza virus vaccination. Ferrets were infected with historical A(H3N2) influenza viruses isolated from either the 1970’s, 1980’s, or 1990’s and then vaccinated with computationally optimized broadly reactive antigens (COBRA) or wild-type (WT) influenza virus like particles (VLPs) expressing hemagglutinin (HA) vaccine antigens to examine the expansion of immune breadth. Vaccines with the H3 COBRA HA antigens had more cross-reactive antibodies following a single vaccination in all three pre-immune regimens than vaccines with WT H3 HA antigens against historical, contemporary, and future drifted A(H3N2) influenza viruses. The H3 COBRA HA vaccines also induced antibodies capable of neutralizing live virus infections against modern drifted A(H3N2) strains at higher titers than the WT H3 HA vaccine comparators.